Determination of environmental safety level with laser-induced breakdown spectroscopy technique - Badday, M. A. (Taylor and Francis Ltd., 2015)
This paper reports the quantitative estimation of heavy metals contamination in the soil, around the power station, by laser-induced breakdown spectroscopy (LIBS). Soil samples were collected from various distances (200–1000 m) and depths (10–50 cm) in the vicinity of the Iskandar power station in Johor, Malaysia. Samples were dried and pelletised prior to excitation. A Q-switched Nd:YAG laser was employed to ablate the sample and MayaPro spectrometer (Ocean Optics) for recording the emission spectrum of laser-induced plasma. Pb, Fe, Ni and Cu concentrations were estimated in the polluted soil with repeatability rate of above 96%. Quantitative results of LIBS were validated by flame atomic absorption spectroscopy (FAAS) and were found in good agreement. The concentration of the detected heavy metal elements was found within the safety limits set by Department of Environment (DOE) of Malaysia and the European standards.